2017
DOI: 10.1590/abd1806-4841.20175171
|View full text |Cite
|
Sign up to set email alerts
|

Severe cutaneous adverse drug reactions of Chinese inpatients: a meta-analysis

Abstract: BackgroundThe rate of severe cutaneous adverse drug reactions is low, and these reactions can result in death or disability. An evidence-based epidemiological study of severe cutaneous adverse drug reactions in China has not been reported.ObjectiveThe aim of this study was to analyze epidemiology and characteristics of severe cutaneous adverse drug reactions of Chinese inpatients during the recent 15 years with meta-analysis.MethodsWe retrospectively reviewed Chinese literature reporting severe cutaneous adver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 15 publications
2
11
0
1
Order By: Relevance
“…[6][7][8][9] Regarding SCARs, the drugs involved depend on the population (adults or children). In this sense, antibiotics and anticonvulsants are the most common ones in adults 10 ; and antibiotics, NSAIDs, and chemotherapeutics 11 as well as aromatic anticonvulsants and also allopurinol are the most frequently involved in children. [12][13][14] Over the last years, DHRs to new drugs as monoclonal antibodies, sulphasalazine and antituberculosis drugs have also been reported.…”
Section: The Burden Of Drug Hyper S En S Itivit Ymentioning
confidence: 99%
“…[6][7][8][9] Regarding SCARs, the drugs involved depend on the population (adults or children). In this sense, antibiotics and anticonvulsants are the most common ones in adults 10 ; and antibiotics, NSAIDs, and chemotherapeutics 11 as well as aromatic anticonvulsants and also allopurinol are the most frequently involved in children. [12][13][14] Over the last years, DHRs to new drugs as monoclonal antibodies, sulphasalazine and antituberculosis drugs have also been reported.…”
Section: The Burden Of Drug Hyper S En S Itivit Ymentioning
confidence: 99%
“…10 SCADRs are in effect a group of delayed-type hypersensitiv- 13 In China, exfoliative dermatitis (ED) is also classified as an SCADR. 14 Studies have shown that SJS is the most frequent clinical subtype of SCADR in China. 14 The study of SCADRs based on litigation cases has not previously been reported, yet this type of research is crucial for improving knowledge of the general characteristics of SCADRs, their causes, associated economic burden and potential preventive measures.…”
Section: What Is K Nown and Objec Tivementioning
confidence: 99%
“…49 (20) c. Inadequate estimation of severity of SCADRs; delayed or missed diagnosis; and improper, non-standard or delayed treatment. 35 (14) Total 251 (100)…”
Section: What Is Ne W and Con Clus I Onmentioning
confidence: 99%
“…However, many skin diseases, it is essential to consider drugs as a possible cause of any eruption, because drug eruptions can take the form of any skin lesion. 11,12 Other than skin diseases and adverse drug reactions some systemic infections can cause skin rashes. 13 The pathophysiology of drug-induced adverse skin eruptions is not exactly known, however, immune-mediated reactions occur as a result of bizarre effects.…”
Section: Discussionmentioning
confidence: 99%